2020
DOI: 10.1038/s41467-020-17243-z
|View full text |Cite
|
Sign up to set email alerts
|

EEF1A1 deacetylation enables transcriptional activation of remyelination

Abstract: Remyelination of the peripheral and central nervous systems (PNS and CNS, respectively) is a prerequisite for functional recovery after lesion. However, this process is not always optimal and becomes inefficient in the course of multiple sclerosis. Here we show that, when acetylated, eukaryotic elongation factor 1A1 (eEF1A1) negatively regulates PNS and CNS remyelination. Acetylated eEF1A1 (Ac-eEF1A1) translocates into the nucleus of myelinating cells where it binds to Sox10, a key transcription factor for PNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 72 publications
3
36
0
Order By: Relevance
“…**p < 0.01 vs Control siRNA group. that the eEF1A1 protein may have therapeutic relevance in diverse conditions with altered neurite outgrowth (McLachlan et al, 2019;Duman et al, 2020). A recent study has suggested that eEF1A1 and CagA cooperated to mediate the expression of IL-6 by affecting the activity of p-STATS727 in the nucleus (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…**p < 0.01 vs Control siRNA group. that the eEF1A1 protein may have therapeutic relevance in diverse conditions with altered neurite outgrowth (McLachlan et al, 2019;Duman et al, 2020). A recent study has suggested that eEF1A1 and CagA cooperated to mediate the expression of IL-6 by affecting the activity of p-STATS727 in the nucleus (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to determine if such biases also exist in cranial neural crest and if different SoxE factors play roles in establishing these predispositions. In addition, there is evidence for direct interaction of Sox factors with epigenetic factors, such as HDACs, to regulate cell fate decisions (Duman et al, 2020). To date, studies of Sox partners/co-factors have predominately focused on other transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of Sox10 in Schwann cells has been linked with eEF1A1 which, upon acetylation, removes SOX10 from the nucleus. In Schwann cells, this activity is blocked by HDAC1/2, Sox10 co-factors essential for myelination, which deacetylate eEF1A1 causing it to return to the cytoplasm and preventing nuclear export of Sox10 (Duman et al, 2020). Finally, one of the essential functions of Sox10 is to direct the neuroglial progenitor cells of the DRG toward the glial lineage.…”
Section: Sox Factors and The Peripheral Nervous Systemmentioning
confidence: 99%
“…A more recent study by Duman et al discovered that theophylline enhanced CNS and PNS remyelination by increasing HDAC2, SOX10 and MBP protein levels in young adults and old mice after inducing a focal demyelinating lesion in the spinal cord. The increased remyelination efficiency of theophylline only occurred in the lesion site [ 77 ]. Ruiz-Perera et al also discovered a potential link between methylxanthines and MS.…”
Section: Multiple Sclerosismentioning
confidence: 99%